Análise da eficiência empresarial do setor de Food Service em uma cidade turística do Brasil: uma abordagem de fronteira estocástica de produção - Cunha, Margarida Noélia de Aguiar (2020)
This study analyzes the efficiency of the food service sector for a sample of companies in the municipality of João Pessoa-PB. The econometric model of stochastic frontier production (SFA) was applied for a final sample of 90 establishments, considering a Cobb-Douglas functional specification type and variables related to billing, labor, location, competition, commercial strategies and satisfactions of customers revealed in digital media. The estimations of the parameters of the frontier model show, in particular, that the number of workers displays an elasticity of 0.87 with the average revenue, companies located on the beach have a revenue 59% higher than those located in other regions of the city and increases of 1% in customer satisfaction increase average sales by 1.04%. Specifically, an efficiency level was estimated, on average, of 68.7% for the food service sector in the capital of Paraíba, with a range of results ranging from 33% to 89%. These results are relevant for identifying benchmarking companies in the sector, as well as assisting in the optimization of resources and expansion of companies’ profitability.